The ROP vesicle release factor is required in adult Drosophila glia for normal circadian behavior - Ng, Fanny S.; Jackson, F. Rob (Frontiers in Cellular Neuroscience, 2015)
We previously showed that endocytosis and/or vesicle recycling mechanisms are essential in adult Drosophila glial cells for the neuronal control of circadian locomotor activity. In this study, our goal was to identify specific glial vesicle trafficking, recycling or release factors that are required for rhythmic behavior. From a glia-specific, RNAi-based genetic screen, we identified 8 glial factors that are required for normally robust circadian rhythms in either a light-dark cycle or in constant dark conditions. In particular, we show that conditional knockdown of the ROP vesicle release factor in adult glial cells results in arrhythmic behavior. Immunostaining for ROP reveals reduced protein in glial cell processes and an accumulation of the Par Domain Protein 1(PDP1) clock output protein in the small lateral clock neurons. These results suggest that glia modulate rhythmic circadian behavior by secretion of factors that act on clock neurons to regulate a clock output factor.